Beberapa Faktor Yang Mempengaruhi Profitabilitas Perbankan di Indonesia - Wuryaningsih, Wuryaningsih; Suci, Damantika Purnama; Sholahuddin, Muhammad (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
The company's financial profitability performance is very important to make a decision on changes in company policy for investors.This study aims to examine the effect of CAR, NPL, NIM, BOPO and LDR on the profitability of banks in Indonesia that are listed on the Indonesia Stock Exchange for the period 2014-2017. The population of this study is the Foreign Exchange National Private Commercial Bank listed on the Indonesia Stock Exchange for the period 2014-2017. The sample used was 18 banks using the Purposive Sampling method. The data analysis technique uses panel data regression with the Fixed Effect method. The results of the study show that CAR and LDR have a positive and not significant effect on ROA, NPL and BOPO which have a negative and significant effect on ROA, NIM has a positive and significant effect on ROA.